FUNGSI BAHASA DALAM IKLAN KAMPANYE PILKADA KOTA PADANG TAHUN 2018 - Efri Yades; Leni Syafyahya (Universitas Andalas, 2019)
Today people tend to use advertisements to promote politics. This is called campaign advertising, one of which is promoting prospective leaders. On the occasion of int. Will be discussed the language functions contained in the campaign proposal on the Regional Election Committee in the City of Padang. To get an explanation of the language found in campaign advertisements, data was collected by listening to the use of language and its function in advertising campaigns. More than that the data that has been collected is analyzed. Based on the results of the data analysis, it was found that the language function was used in campaign advertisements in the Regional Election Commission in the City of Padang. The language in the campaign advertisements is expresssive, informative and directive.